Long-term evolution of lung function in individuals with alpha-1 antitrypsin deficiency from the Spanish registry (REDAAT) - Esquinas, Cristina (Int J Chron Obstruct Pulmon Dis, 2018)
BACKGROUND: The clinical course of alpha-1 antitrypsin deficiency (AATD) is very heterogeneous. It is estimated that 60% of individuals with severe AATD (Pi*ZZ) develop emphysema. The main objective of this study was to describe the outcomes of long-term lung function in individuals with AATD-associated emphysema after at least 8 years of follow-up. MATERIALS AND METHODS: We performed a retrospective analysis of longitudinal follow-up data of AATD PiZZ patients from the Spanish registry (AATD Spanish Registry [REDAAT]). The main follow-up outcome was the annual rate of decline in forced expiratory volume in 1 second (FEV(1)) calculated using the FEV(1) values at baseline and in the last post-bronchodilator spirometry available. RESULTS: One hundred and twenty-two AATD PiZZ patients were analyzed. The median follow-up was 11 years (interquartile range =9–14). The mean FEV(1) decline was 28 mL/year (SD=54), with a median of 33 mL/year. Tobacco consumption (β=19.8, p<0.001), previous pneumonia (β=27.8, p=0.026) and higher baseline FEV(1)% (β=0.798, p=0.016) were independently related to a faster FEV(1) decline. CONCLUSION: In this large cohort with a long follow-up, we observed a very variable decline of FEV(1). However, the mean FEV(1) decline was similar to that observed in large cohorts of smoking-related COPD. Tobacco consumption, previous pneumonia and better lung function at baseline were related to a faster decline in FEV(1). These results highlight the importance of early diagnosis and effective treatment.